High-throughput analysis unveils a highly shared satellite DNA library among three species of fish genus Astyanax - De Silva, Duílio M.Z.A. [UNESP]; Utsunomia, Ricardo [UNESP]; Ruiz-Ruano, Francisco J.; Daniel, Sandro Natal [UNESP]; Porto-Foresti, Fábio [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Oliveira, Claudio [UNESP]; Camacho, Juan Pedro M.; Foresti, Fausto [UNESP] (Springer Nature, 2017)
The high-throughput analysis of satellite DNA (satDNA) content, by means of Illumina sequencing, unveiled 45 satDNA families in the genome of Astyanax paranae, with repeat unit length (RUL) ranging from 6 to 365 bp and marked predominance of short satellites (median length = 59 bp). The analysis of chromosomal location of 35 satDNAs in A. paranae, A. fasciatus and A. bockmanni revealed that most satellites are shared between the three species and show highly similar patterns of chromosome distribution. The high similarity in satellite DNA content between these species is most likely due to their recent common descent. Among the few differences found, the ApaSat44-21 satellite was present only on the B chromosome of A. paranae, but not on the A or B chromosomes of the two other species. Likewise, the ApaSat20-18 satellite was B-specific in A. paranae but was however present on A and B chromosomes of A. fasciatus and A. bockmanni. The isochromosome nature of B chromosomes in these species was evidenced by the symmetric location of many satDNAs on both B chromosome arms, and the lower symmetry observed in the A. fasciatus BfMa chromosome suggests that it is older than those analyzed in A. paranae and A. bockmanni.